Discussion of Growth And Content of Papain In Papaya Callus (Carica Papaya L.) By Tissue Culture Technique With Elicitor Saccharomyces Cerevisiae Treatment In Ms And Vw - Sri Arijanti; Dwie Retna Suryaningsih; Arief Eryanto (Agricultural Science, 2018)
Plants of papaya were have the main sources of chemical compounds that were generally used in pharmaceuticals and food-additive industries. One of the effort to increase the content of Papain in papaya is through tissue-culture and elicitation technique.The purposes of this research are *To investigate the content of Papain in calluses of papaya leaves with treatment of elicitor Saccharomyces cerevisiae in MS and VW mediums. This research was conducted in the month of November 2017 to January 2018, using Complete Random Design (CRD) with factorial using two factors, repeated four times and each repitition contained 4 samples. The main results of this research had shown that The treatment of VW medium and elicitor Saccharomyces cerevisiae 25 mg Dry Matter/L had produced the highest content of Papain.